The Relationship of Learning Motivation to Student Learning Outcomes at the Institute of Computer Data Training Course in Padang City - Elza Algusli Melinda; Rini Rahmadani; Utari Handayani; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research is to see how the development of science in the field of non-formal education, especially in training in the field of computer-related to students in the training and also aims to arouse students' enthusiasm for learning in science that is in the educational profession outside of school. Namely training and education. In this institution it is important to recognize and facilitate the learning motivation found in these students. By providing learning resources to be able to increase learning motivation in these learners, so they can take learning seriously and can also improve the quality of learning at primary computer data course institutions. In education and training is something that can be useful for someone and initial capital to improve their skills and also improve skills and abilities for someone who does not know their skills and abilities and can also produce productivity at work, both those who have worked and want to get certain skill.Keywords: Training, Learning Motivation, Learning Outcomes